2021
DOI: 10.5424/sjar/2020184-16244
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Pepino mosaic virus, a new threat for Serbia’s tomatoes

Abstract: Aim of study: To report the occurrence of Pepino mosaic virus (PepMV) on tomato in Serbia and to genetically characterize Serbian PepMV isolates.Area of study: Tomato samples showing virus-like symptoms were collected in the Bogojevce locality (Jablanica District, Serbia).Material and methods: Collected tomato samples were assayed by DAS-ELISA using antisera against eight economically important or quarantine tomato viruses. Three selected isolates of naturally infected tomato plants were mechanically transmitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In tomato, fruit marbling symptoms are considered as the most important cause of significant economic losses around the world (Hanssen and Thomma, 2010;Hanssen et al, 2010b). PepMV is present in major tomato-growing areas of the Mediterranean (Gómez et al, 2012) and was recently reported in United States and Mexico (Ling and Zhang, 2011), South Africa (Carmichael et al, 2011), Spain and Morocco (Gómez-Aix et al, 2019), and Serbia (Stanković et al, 2020).…”
Section: Potexvirus: Pepino Mosaic Virus (Pepmv)mentioning
confidence: 99%
“…In tomato, fruit marbling symptoms are considered as the most important cause of significant economic losses around the world (Hanssen and Thomma, 2010;Hanssen et al, 2010b). PepMV is present in major tomato-growing areas of the Mediterranean (Gómez et al, 2012) and was recently reported in United States and Mexico (Ling and Zhang, 2011), South Africa (Carmichael et al, 2011), Spain and Morocco (Gómez-Aix et al, 2019), and Serbia (Stanković et al, 2020).…”
Section: Potexvirus: Pepino Mosaic Virus (Pepmv)mentioning
confidence: 99%